Study of transonic effect of flows around slender bodies of revolution and plane profiles - Ngoc, Hoang Thi Bich (Vietnam Journal of Mechanics, 2010)
Transonic effect with presence of local supersonic terminated by shock wave is not wished. In spite of wishes or not, the appearance of shock waves is not avoided. Strong shock waves cause losses, even a grand decrease of aerodynamic quality in fluid-solid interaction. However, under certain conditions, transonic effect increases the drag and at the same time increases the lift leading the amelioration of aerodynamic quality. This work uses numerical methods and established programs for solving differential equations of the axisymmetric flow and the plane flow to study the influence of transonic effects for the two cases.